(A study on characteristics of dough made From sweet Potato Flour and Wheat Flour) - M Maman Rohaman; Novianis -; Endah Djubaedah (Balai Besar Industri Agro, 1987)
A study to substitute sweet potato flour for wheat flour dough has been conducted using two type of wheat flour and various percentage of substitution. To test the degree of substitution, the characteristics of dough were measured using Brabender farinograph and Brabender Extensograph. Measurement of rheological properties using farinograph showed that the dough made of 60% sweet potato flour with hard wheat and those of 40% sweet potato flour with medium wheat cannot be done. Viscoelasticity of dough from 40% or more sweet potato flour with hard or medium wheat cannot be measured using Extensograph.